2002
DOI: 10.1002/hep.1840360612
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of long-term carvedilol and propranolol administration in the treatment of portal hypertension in cirrhosis

Abstract: Short-term carvedilol administration is more powerful than propranolol in decreasing hepatic venous pressure gradient (HVPG) in cirrhotic patients, but induces arterial hypotension that may prevent its long-term use in portal hypertensive patients. This study compared the HVPG reduction and safety of long-term carvedilol and propranolol. Fifty-one cirrhotic patients were randomly assigned to receive carvedilol (n = 26) and propranolol (n = 25). Hemodynamic measurements and renal function were assessed at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 27 publications
6
128
2
1
Order By: Relevance
“…Similar observations of a reduction of heart rate and cardiac index have been demonstrated in cirrhotic patients receiving either acute or chronic carvedilol. [21][22][23][24] However, we found that chronic carvedilol administration did not affect mean arterial pressure in cirrhotic rats. Similarly, previous studies have shown that chronic administration of carvedilol in patients with cirrhosis causes a smaller reduction or an insignificant change in mean arterial pressure than acute administration.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Similar observations of a reduction of heart rate and cardiac index have been demonstrated in cirrhotic patients receiving either acute or chronic carvedilol. [21][22][23][24] However, we found that chronic carvedilol administration did not affect mean arterial pressure in cirrhotic rats. Similarly, previous studies have shown that chronic administration of carvedilol in patients with cirrhosis causes a smaller reduction or an insignificant change in mean arterial pressure than acute administration.…”
Section: Discussioncontrasting
confidence: 49%
“…20 Hemodynamic studies in patients with cirrhosis have found that carvedilol effectively decreases portal pressure without compromising hepatic blood flow or renal function. [21][22][23][24][25] A recent study reported that carvedilol has a greater portal hypotensive effect than propranolol alone in patients with cirrhosis. 23 The current study was undertaken to evaluate the possible mechanism of carvedilol on hemodynamics in cirrhotic rats with portal hypertension.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, only around half the patients reach an appropriate hemodynamic response with this treatment. It has been suggested that carvedilol [31], or the combination of propranolol and prazosin [32], may significantly increase this rate of response. However, these medications also induce a higher proportion of side effects, mainly arterial hypotension and fluid retention [31,32].…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that carvedilol [31], or the combination of propranolol and prazosin [32], may significantly increase this rate of response. However, these medications also induce a higher proportion of side effects, mainly arterial hypotension and fluid retention [31,32]. Obviously, other pharmacological options devoid of systemic effects should be evaluated to enhance the portal hypotensive effect achieved with the medications currently available [2,33].…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated to cause a reduction in portal pressure through decreased splanchnic blood flow and decreased portocollateral resistance (66,67). Carvedilol has also been shown to be superior to other beta-blocking agents in reducing the hepatic venous pressure gradient (66,68).…”
Section: Pre-operative Cardiovascular Assessment and Managementmentioning
confidence: 98%